PRODUCTION AND CHEMICAL CHARACTERIZATION OF BIOCHAR FROM ORGANIC AGRICULTURAL WASTE - Trujillo A, Enmer (2019)
The intensive poultry systems generate organic waste (poultry manure and poultry litter); which, when used fresh, cause negative impacts to the environment, however, these organic residues are rich in nutrients that can be used as soil amendments, being the biochar production an alternative for their use. In this investigation, the biochar production was carried out with a pyrolyzing furnace (5 kg capacity). Measuring in the production stage the parameters: temperature, yields and density of the resulting material. Likewise, the raw material (chicken and poultry litter) and the biochar obtained were characterized, determining: pH, humidity, ash, total organic carbon and contents of the macro and micronutrients. When evaluating the properties of the biochar, statistically significant differences were obtained between the poultry litter and chicken manure in yields, density, pH, humidity, ash, nitrogen, total phosphorus, calcium, magnesium and iron. The biochar was subjected to bioassay tests to determine the growth rate of the seeds and the growth of the stems of the first ten days. The germination rate of the biochar of the chicken manure was significant with the treatment of 3% and as a consequence the length of growth of the stems of the seedlings was significant.